Transformasi Lahan dan Perubahan Nafkah Rumah Tangga di Desa Hatusua, Kecamatan Kairatu, Kabupaten Seram Bagian Barat - Delvien Lodarmasse; Junianita F. Sopamena; Jeter D. Siwalette (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to analyze the land transformation that occurred in Hatusua Village and to analyze land transformation on household income in Hatusua Village. The research location was chosen purposively (purposive random sampling). The population in this study was 198 farmers, the determination of the sample was based on Arikunto's research considerations. If the total population is less than 100 people, the total sample is taken as a whole, but if the population is greater than 100 people, then 10-15% or 20-25% of the population size. The number of samples to be taken in this study were 29 farmers or 15% of the population of 198 farmers. The research method uses descriptive qualitative. The results showed that the village of Hatusua had experienced a land transformation which had an impact on the livelihood of the farmer's household due to the presence of the company PT Spice Island Maluku (SIM) which controlled the community's lands for the cultivation of abaka bananas, which it was known that before the company the land was used by farmers to grow crops. However, from renting land that is carried out, farmers lose their rights to ownership and control of land is reduced, so farmers have to do additional work outside of their jobs as daily laborers in the company so that consumption and family needs are still met.